Real‐World Study of EGFR‐TKI Rechallenge With Another TKI After First‐Line Osimertinib Discontinuation in Patients With EGFR‐Mutated Non‐Small Cell Lung Cancer: A Subset Analysis of the Reiwa Study - Kei Sonehara; Kazunari Tateishi; Kiyotaka Yoh; Kazuhiro Usui; Yukio Hosomi; Kazuma Kishi; Go Naka; Kageaki Watanabe; Shu Tamano; Kohei Uemura; Hideo Kunitoh (Thoracic Cancer)
ABSTRACT Introduction First‐line osimertinib is widely used to treat patients with epidermal growth factor receptor (EGFR)‐mutated non‐small cell lung cancers (NSCLC). In clinical practice, rechallenge therapy with another EGFR‐tyrosine kinase inhibitor (TKI) is often performed after first‐line TKI discontinuation owing to resistance or toxicity; however, the efficacy and toxicity of EGFR‐TKI rechallenge after first‐line osimertinib have not been adequately investigated. This study aimed to examine the efficacy and safety of EGFR‐TKI rechallenge with another TKI. Methods This multicenter prospective observational study enrolled patients with EGFR‐mutated NSCLC who received first‐line osimertinib and another EGFR‐TKI as second‐ or third‐line treatment between September 2018 and August 2020. Results Fifty‐three patients received rechallenge with another EGFR‐TKI in the second‐line (n = 38, 71.7%) or third‐line (n = 15, 28.3%) setting. The primary reason for first‐line osimertinib discontinuation was toxicity in 32 (60.4%, 17 patients with pneumonitis) and disease progression in 20 (37.7%) patients. The most common rechallenge EGFR‐TKI was afatinib (n = 24, 45.3%), followed by gefitinib (n = 16, 30.2%) and erlotinib (n = 8, 15.1%). The real‐world time to treatment failure (rwTTF) was 7.3 months. The rwTTF for the toxicity discontinuation and progressive disease discontinuation groups was 9.3 months and 5.1 months, respectively, (HR 1.61, p = 0.119). EGFR‐TKI rechallenge was discontinued due to toxicity in nine patients (17.0%), but no patient developed pneumonitis. Conclusion EGFR‐TKI rechallenge with another TKI is well tolerated in patients with EGFR‐mutated NSCLC. Thus, it may be a useful treatment option after first‐line osimertinib failure, especially after osimertinib discontinuation due to toxicity.